Dependent Nationalism - Magno, Alexander R. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
When the treaty governing the use of Philippine military facilities by the US was being renegotiated, the air was thick with officially sanctioned anti-Americanism. Obeisant Filipino bureaucrats kept a minor but constant barrage against the iniquities of Filipino-American “special relations.” Academics discoursed on the “love-hate” relationship between the two. When the US conceded to a “compensation package,” the nationalist rhetoric abated. When more serious nationalists demanded the withdrawal of American military facilities on Philippine soil, new public debate was rudely ended with the announcement of the new treaty. The US Congress proposed to modify the “compensation package” by cutting military aid while boosting economic assistance. In addition, they proposed to channel a portion of the economic assistance through the Philippine Catholic Church and required the American President to report to Congress on Philippine political and economic progress. This proposal was met with a threat by the Marcos government to abrogate the bases treaty and grounds since it was greatly dependent on foreign development and military aid, especially in the ongoing economic crisis at the time. The economic deterioration and general insecurity over the political legitimacy of the regime have diminished the basis of support for the Marcos faction, forcing them to rely more on military control to maintain political supremacy. There was mounting pressure to move government resources away from the military. Scandals of property holdings and a campaign for impeachment were answered by impending reimposition of martial rule, underscoring the government’s reliance on the military. The proposal of the American Congress threatened the very structure of the Marcos government and through bluff and bluster, the latter concededly won this round when the two additions to the proposal were dropped. But whatever gains were made would not cure the regime’s vulnerabilities. The last exchange merely exposed them.
Keywords: treaty on Philippine military bases, United States, Philippines, US Congress, Philippine Catholic Church, Marcos regime, nationalism